Elections to the Councils of Central Black Earth Region at 1929 - Alexander Yurievich Saran (Управленческое консультирование)
The article analyzes the election campaign of 1929 in the local and Central Soviets in the Soviet Union at the regional level on the example of Central Black Earth Region. On materials of archives and published documents examines the struggle over the election between social groups and regional elites with the involvement of the political police. It concludes that the party-state apparatus by the early 1930s gradually taking control of society.